Comparison of ELISA and IFAT for Leishmania infantum by European and Middle Eastern diagnostic laboratories - Kurayi G. Mahachi; Marie Ozanne; Patrick Bourdeau; Juliana Sarquis; Eric Kontowicz; Laia Solano-Gallego; Luis Cardoso; Gaetano Oliva; Gad Baneth; Maria Grazia Pennisi; Angela M. Toepp; Guadalupe Miró; et al. (Parasites & Vectors)
Abstract Background Visceral leishmaniosis (VL) is the most severe form of human leishmaniosis, with an estimated 95% case fatality if left untreated. Dogs act as peridomestic reservoir hosts for the protozoan parasite Leishmania infantum, a causative agent for human leishmaniosis, endemic throughout the Mediterranean basin. To assure consistent and accurate surveillance of canine infection and prevent transmission to people, consistent diagnosis of canine L. infantum infection across this region is essential for protecting both human and animal health. Our goal was to compare the accuracy, sensitivity and specificity of enzyme-linked immunosorbent assays (ELISA) and immunofluorescence antibody tests (IFAT), performed at seven academic veterinary diagnostic centres across southern Europe and Israel. Methods We performed a known sample “ring” trial to compare L. infantum quantitative serological tests. Two hundred seventy-two (n = 272) canine serum samples of known serological status were chosen from these sites, representative of the region. In-house or commercial ELISA and IFAT were performed according to each laboratory’s specifications. Latent Class Analysis (LCA) was used to determine sensitivity and specificity of each test. True and false positives were calculated to determine the probability of identifying samples. Results Sensitivity and specificity for ELISA ranged from 95 to 99% and 92% to 97%, respectively, with moderate variability from one site. Sensitivity and specificity for IFAT ranged from 89 to 99% and 83% to 94%, respectively, with increased variability compared to ELISA. Overall test agreement was 78% with a pair-wise agreement between 65 and 89%. Conclusions All sites demonstrated substantial comparative diagnostic accuracy, with good agreement based on known seropositive and seronegative samples. Studies and interventional trials that use these tests will remain valid because of high diagnostic agreement between sites. Graphical Abstract